Reading without limits : teaching strategies to build independent reading for life - Witter, Maddie 1979- (San Francisco, Calif. : Jossey-Bass, A Wiley Imprint, 2013)
'Imagine a classroom where all students are engaged in highly rigorous and fun learning every single day. That classroom can be yours starting tomorrow.This handy guide gives teachers, schools, and districts the support they need to help their students achieve dramatic academic gains and become lifelong readers. Students will be raised to the highest level of fervor, love of learning, stamina, and independent thinking.Reading Without Limits provides a unique structure based on choice, shared, and guided reading that rigorously prepares students for high-level literacy achievement.Written for real teachers (who work late hours grading tests, making bulletin boards, coaching basketball games, and getting phone calls about homework), Reading Without Limits keeps things practical. Structured in'mild','medium', and'spicy' action steps, teachers and school leaders can mix and match the tools presented in order to fit the individual needs of their students. All tools are written so that they can be implemented on Monday. Also included: Lesson plans Reading strategies that align with Common Core State Standards Reading assessments Options for special needs students A chapter on how to integrate standardized testing You don't have to be a reading specialist to pick up this book. Anyone who wants to dramatically improve reading achievement will find helpful suggestions. You might be a third grade teacher whose students have mastered decoding, and you are ready to build their comprehension. Or you might be a high school science teacher whose students aren't yet reading on level with deep critical thinking. This book is for you. It doesn't matter whether you are a public, charter, private, or alternative education teacher: the Reading Without Limits program works in each one. Along with hundreds of ready-to-use teaching strategies, Reading Without Limits comes with a supplemental website where teachers can download even more resources for free!Reading Without Limits is the first book offered in the KIPP: Educator Series. KIPP, or the Knowledge is Power Program, began in 1994. As of Fall 2012, there are 125 KIPP schools in 20 states and the District of Columbia serving over 40,000 students climbing the mountain to and through college'--
Includes bibliographical references (pages 362-369) and index.
Keywords: Children -- Books and reading; Literacy; Reading; Reading promotion; EDUCATION / Teaching Methods & Materials / General